ІLLEGAL AND UNCONTROLLED AMBER’S EXTRACTION AND MEASURES TO COMBAT IT - Kuchynska, O.; Nesterovskyi, V.; Starenkyi, O.; Tsyganyuk, Y. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Significant increase in the demand for amber in the world gave rise to a multitude of complex problems in Ukraine, related not only to geology and mineral resources use, but also economy, legislation and other aspects of life. The prevention and control of crimes related to illegal amber’s extraction are provided through various activities and methods. One of them is the implementation of the laws of Art. 240 of the Criminal Code of Ukraine through criminal prosecution. It is implemented by applying rules of criminal procedural law: individuals’ actions qualification during adding data to the Unified Register of pre-trial investigations, enforcement of criminal proceedings, evidence providing in cases involving illegal amber’s extraction, etc. Thus, as a consequence, there is a necessity to conduct theoretical and legal analysis, to develop practical recommendations to ensure the effective application of combatting measures against illegal amber’s extraction during the implementation of evidence in criminal proceedings. In particular, the authors emphasize among these measures specific unspoken investigative actions, as they can provide appropriate, valid and credible evidence against illegal extraction of amber; individuals’ actions qualification with the availability of actual grounds, which indicate commiting of moderate gravity crime, provided for by part 2, part 3 of Article 240 of the Criminal Code of Ukraine and Part 4 of Article 240 of the Criminal Code of Ukraine is defined as unjustified. In order to avoid issues mentioned above, it has been proposed to assume the possibility of conducting unspoken investigative activities in the current Criminal Procedural Code of Ukraine not only in relation to grave crimes or felonies, but also in relation to crimes of moderate gravity.